Fostering Exemplary Character Through Physical Activities in Physical Education Learning - Salahudin, Salahudin; Nurgufriani, Anita; Muhammad, Muhammad (Yayasan Insan Mulia Bima, 2024)
Physical Education (PE) is an integral component of the educational curriculum that serves not only to enhance students' health and physical fitness but also to cultivate exemplary character traits. Qualities such as discipline, teamwork, responsibility, sportsmanship, and honesty can be fostered through well-designed physical activities. This study aims to analyze the implementation of physical activities in PE learning as a medium for character development. The method employed is qualitative with a descriptive approach. Data were collected through interviews, observations, and document analysis conducted in several junior high schools, including SMPN 2 Bima. The findings reveal that physical activities can effectively instill positive character values when implemented with proper planning and guidance. Discipline can be developed through structured exercises and adherence to game rules. Team-based activities, such as ball games and relay races, provide opportunities for students to learn teamwork and leadership. Sportsmanship and emotional control are observed to improve in competitive situations, while responsibility and honesty can be cultivated through active student participation in maintaining sports equipment and complying with game rules. By integrating character values into PE learning, physical activities not only function as a medium for motor skill development but also serve as a tool for holistic character education. This study recommends that PE teachers optimize the potential of physical activities as a medium for character education by designing lessons that focus not only on physical outcomes but also on fostering students' moral and social values.